Cassava Wastewater Treatment in Fixed-Bed Reactors: Organic Matter Removal and Biogas Production - Watthier, Elisangela; Andreani, Cristiane L.; Torres, Douglas G. B.; Kuczman, Osvaldo; Tavares, Maria H. F.; Lopes, Deize D.; Gomes, Simone D. (Frontiers in Sustainable Food Systems, 2019)
The process of cassava starch extraction is associated with the generation of a large volume of liquid wastes from root washing and starch extraction (5 to 7 L.kg−1root). In this context, the aim of this study was to evaluate the treatment of cassava starch wastewater in a horizontal anaerobic fixed bed reactor to the removal of organic matter and generation of biogas. For this purpose, two fixed bed reactors filled with different types of support materials were used: bamboo rings (R1) and flexible PVC rings (R2). The reactors were constructed in polyvinyl chloride (PVC) with 90 cm length and 15 cm diameter. To evaluate the reactors were carried out 13 assays (A1 to A13) with increases in the organic loading rate (OLR, 1.7 to 15.0 g.L−1.d−1) and a decrease in the hydraulic retention time (HRT, 4.0 to 0.8 days). Biogas production followed a similar pattern in both reactors. The highest biogas productions of 1.4 L.L−1.d−1 (R1) and 1.0 L.L−1.d−1 (R2) were verified in the assay A6 in which were applied highest influent concentration (15.1g.L−1), intermediates OLR (5.6 g.L−1.d−1) and HRT (2.7 d). The chemical oxygen demand (COD) removal increased with the OLR increase resulting in COD removal values of up to 99%. Total solids removal efficiencies of 86.2 and 85.5% were achieved in R1 and R2, respectively. In both reactors, the contact surface of bamboo (132 m2.m−3) and PVC (191 m2.m−3) supported biomass attachment even in the highest OLR (15 g.L−1.d−1) and low HRT (0.8 d). Both support material provided conditions to the reactors resist the variations in operating conditions and reestablish the equilibrium after possible hydraulic and organic shocks load, constituting a robust system for the treatment of cassava starch wastewater. In these conditions the COD and solids removal remained satisfactory. After a 450-days reactor running, no changes were observed in the composition and structure of the support material, indicating that bamboo and PVC are possible cheap and efficient alternatives for biomass immobilization.